2008
DOI: 10.1016/j.parkreldis.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychosocial factors associated with fatigue in patients with Parkinson's disease

Abstract: Fatigue is an important contributor to poor quality of life. The aim of our research was to identify factors associated with fatigue among patients with Parkinson's disease (PD). The sample consisted of 150 patients. The Multidimensional Fatigue Inventory (MFI), Unified Parkinson's Disease Rating Scale (UPDRS), Hospital Anxiety and Depression Scale (HADS) and Charlson co-morbidity index were used for analysis. Demographic data were obtained in a structured interview. T-test, chi(2)-test and general linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
8
33
2
1
Order By: Relevance
“…The higher prevalence of fatigue in PD, however, cannot be explained only by older age. In contrast with our finding, most previous studies found no association between older age and fatigue in PD [11,17]. A recent study on fatigue in early PD found a significant correlation between higher fatigue scores and older age, but when linear regression analysis was applied, only depression and UPDRS activities of daily living subscale remained significant in their population [38].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The higher prevalence of fatigue in PD, however, cannot be explained only by older age. In contrast with our finding, most previous studies found no association between older age and fatigue in PD [11,17]. A recent study on fatigue in early PD found a significant correlation between higher fatigue scores and older age, but when linear regression analysis was applied, only depression and UPDRS activities of daily living subscale remained significant in their population [38].…”
Section: Discussioncontrasting
confidence: 99%
“…We found the prevalence of fatigue to be higher than is described in previous studies [15][16][17], which mostly used uni-dimensional fatigue rating scales. MFI scores and the prevalence of fatigue are significantly higher in the physical domains of fatigue in both groups than in the mental domains, which could be explained by the stronger impact of core motor features of PD on the physical abilities of patients [11]. Both primary and secondary fatigue differed significantly in baseline characteristics and factors associated with different fatigue domains.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Fatigue is multifactorial and has been set as a general sense of tiredness or difficulties in starting an activity on the physical or mental sector experienced by an individual during many days or weeks [5]. Nearly 58% of patients with PD present fatigue [2] [6], with higher incidence in advanced stages of PD [7]. Fatigue is linked with serotonergic dysfunction in basal ganglia and limbic circuits [8] [9], and in thalamus, additional cortical and striatal regions [10].…”
Section: Introductionmentioning
confidence: 99%